The DESIGN OF ROLLER ON WHEELS REMOVAL AND INSTALLER AIDS ON ANOA PANSER COMBAT VEHICLE: Rancang Bangun Roller Pada Alat Bantu Pelepas Dan Pemasang Roda Pada Kendaraan Tempur Panser Anoa - Nur Aziz Hamid Maryanto; Fajar Apit; Ismanto Setyabudi (Jurnal Otoranpur, 2021)
The Army has a combat vehicle Panser ANOA 6x6 which is produced by PT. Pindad. The Panzer model combat vehicle has a number of 6 large wheels with a diameter of 1300 mm and a weight of 250 Kg on each wheel. A large number of vehicles are not supported by 'Special tool' or equipment that has a function to facilitate heavy work that has a high risk of work accidents. Therefore, a Panser wheel release and installer are made with a Roller buttress as a lift pad and the Panser wheel player is quite operated by one personnel. The method used in this study is an experimental method to find out the results of analysis on roller and wheel installer Panser ANOA 6x6. The loading received at roller construction is 1226.25 N, the bending pressure of the shaft is 546.18 N/mm2, the bending moment of the shaft is 429.19 Nm, the shaft mass is 1.7 Kg. The Roller tube flexing pressure is 879.05 N/mm2, the bending moment is 416.93 Nm and the Roller tube mass is 2.84 Kg. Welding Pressure Roller is 0.325 N/mm2. Faced with the modulus value of ST40 steel elasticity, roller construction is very capable of receiving panzer Anoa 6x6 wheel load. Keywords: Construction, Roller, Pressure, Moment